Use of Standardized Uptake Value Ratios Decreases Interreader Variability of [(18)F] Florbetapir PET Brain Scan Interpretation - Nayate, A.P. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: Fluorine-18 florbetapir is a recently developed β-amyloid plaque positron-emission tomography imaging agent with high sensitivity, specificity, and accuracy in the detection of moderate-to-frequent cerebral cortical β-amyloid plaque. However, the FDA has expressed concerns about the consistency of interpretation of [(18)F] florbetapir PET brain scans. We hypothesized that incorporating automated cerebral-to-whole-cerebellar standardized uptake value ratios into [(18)F] florbetapir PET brain scan interpretation would reduce this interreader variability. MATERIALS AND METHODS: This randomized, blinded-reader study used previously acquired [(18)F] florbetapir scans from 30 anonymized patients who were enrolled in the Alzheimer's Disease Neuroimaging Initiative 2. In 4 separate, blinded-reading sessions, 5 readers classified 30 cases as positive or negative for significant β-amyloid deposition either qualitatively alone or qualitatively with additional adjunct software that determined standardized uptake value ratios. A κ coefficient was used to calculate interreader agreement with and without the use of standardized uptake value ratios. RESULTS: There was complete interreader agreement on 20/30 cases of [(18)F] florbetapir PET brain scans by using qualitative interpretation and on 27/30 scans interpreted with the adjunct use of standardized uptake value ratios. The κ coefficient for the studies read with standardized uptake value ratios (0.92) was significantly higher compared with the qualitatively read studies (0.69, P = .006). CONCLUSIONS: Use of standardized uptake value ratios improves interreader agreement in the interpretation of [(18)F] florbetapir images.